Effect of Pruning Severity and Nutrient Application on Growth, Yield and Quality of Ber cv. Banarasi Karaka - Kumar, Vikas; Tripathi, V. K.; Kumar, Amit (International Journal of Bio-resource and Stress Management, 2025)
The present investigation was carried out during rabi (October, 2024 to March, 2025) at Horticulture Garden, Department of Fruit Science of Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, U.P, India, entitled Effect of Pruning Severity and Nutrient Application on Growth, Yield and Quality of ber (Zizyphus mauritiana Lamk.) cv. Banarasi Karaka in a Randomized Block Design with nine treatments and three replications. The study revealed significant variations in growth, yield and quality parameters due to different combinations of fertilizers, organics and biofertilizers. Among the treatments, application of 50% RDF, vermicompost 2 kg, Azotobacter 100 g, PSB 100 g, and Azospirillum 100 g (T7) consistently outperformed others by recording the highest vegetative growth viz., shoots 34.14, shoot length 4.05 m, diameter 3.45 cm and canopy spread 32.15 m², fruit morphometric traits viz., length 3.57 cm, diameter 3.30 cm, weight 21.89 g, volume 22.13 ml, pulp 20.03 g, stone 1.85 g and yield (30.11 kg plant-1). Quality parameters were also maximized under treatment T7, with the lowest acidity (0.13%) and superior values for TSS (20.47°Brix), TSS: acid ratio (146.27), ascorbic acid (70.13 mg (100 g)-1), and total sugars (9.26%). The treatment (T8) with 75% RDF, Vermicompost 2 kg, Azotobacter (100 g), PSB (100 g) ranked second, while control (T1) consistently recorded the lowest values across all attributes. The results clearly demonstrated that the integrated application of organics, biofertilizers, and reduced chemical fertilizers not only enhanced vegetative growth and yield but also improved fruit quality, highlighting T7 as the most effective treatment for sustainable berry production.